Palaeography of manuscript collections of Azerbaijani proverbs - Aliyev, Ali Mammadbaghir (Technium Social Sciences Journal, 2022)
Even though it is impossible to determine when proverbs and sayings developed as one of the most common genres of folk literature, its history is closely related to the formation of oral speech and the enrichment of the shades of the meaning of the language. Even though proverbs and sayings turned out to be an integral part of oral speech and were occasionally recorded in epics, fairy tales, and folk stories in classical literature, particularly in large-volume works of written folklore literature, this part of paremiological units was not recorded in a separate collection, and perhaps there was no need for it in the Middle Ages. Because proverbs that are brief in form, deep in meaning, and distinguished for their accurate direction of thought during conversation are simpler, easier to remember, and less likely to be forgotten compared to epics and large-scale folkloric writings. This explains why there are so few collections of proverbs and sayings compared to epics and extensive folklore works of other genres that were recorded in earlier times. In general, today, we consider a written version of any epic, fairy tale, narrative, or other oral folk literature to be a rare literary work if it is discovered in a treasure, a private archive. The scientific community always reacted to such findings with great interest and attention. Therefore, the focus of folklore studies has always been on the sources in which proverbs were recorded.